On-site bundled rapid HIV/HCV testing in substance use disorder treatment programs: study protocol for a hybrid design randomized controlled trial. Issue 1 (December 2016) - Frimpong, Jemima; D'Aunno, Thomas; Perlman, David; Strauss, Shiela; Mallow, Alissa; Hernandez, Diana; Schackman, Bruce; Feaster, Daniel; Metsch, Lisa
Abstract Background More than 1.2 million people in the United States are living with human immunodeficiency virus (HIV), and 3.2 million are living with hepatitis C virus (HCV). An estimated 25 % of persons living with HIV also have HCV. It is therefore of great public health importance to ensure the prompt diagnosis of both HIV and HCV in populations that have the highest prevalence of both infections, including individuals with substance use disorders (SUD). Methods/design In this theory-driven, efficacy-effectiveness-implementation hybrid study, we will develop and test an on-site bundled rapid HIV/HCV testing intervention for SUD treatment programs. Its aim is to increase the receipt of HIV and HCV test results among SUD treatment patients. Using a rigorous process involving patients, providers, and program managers, we will incorporate rapid HCV testing into evidence-based HIV testing and linkage to care interventions. We will then test, in a randomized controlled trial, the extent to which this bundled rapid HIV/HCV testing approach increases receipt of HIV and HCV test results. Lastly, we will conduct formative research to understand the barriers to, and facilitators of, the adoption, implementation, and sustainability of the bundled rapid testing strategy in SUD treatment programs. Discussion Novel approaches that effectively integrate on-site rapid HIV and rapid HCV testing are needed to address both the HIV and HCV epidemics. If feasible and efficacious, bundled rapid HIV/HCV testing may offer a scalable, potentially cost-effective approach to testing high-risk populations, such as patients of SUD treatment programs. It may ultimately lead to improved linkage to care and progress through the HIV and HCV care and treatment cascades. Trial registration ClinicalTrials.gov:NCT02355080 . (30 January 2015)